An optimal grid-connected strategy for improving the DC voltage utilization rate by increasing the number of PV modules connected in series in the string. (1st April 2022) - Zhang, Zhixiang; Ma, Mingyao; Wang, Hai; Yun, Ping
Graphical abstract: Highlights: A low-cost device integrated in the junction box is used to limit PV module voltage. The circuit design and operation principle of the device are analyzed. The DC voltage utilization rate of PV system can be improved by the device. A MPPT voltage control strategy is proposed to release the device. The method has great practical application value and economic saving potential. Abstract: The further reduction of the cost can improve the competitiveness of PV power generation in practice. This work proposes a low-cost hardware circuit integrated in the PV module junction box, which can increase the DC voltage utilization rate and capacity ratio of the system by limiting the voltage of the PV modules to increase the number of modules in series. According to the I-V characteristics, the theoretical optimal proportion of short-circuited cells in the PV module is analyzed. Based on the structure of the actual PV modules, a strategy of limiting the voltage of a single PV substring in the module is implemented. In order to avoid the power loss caused by the voltage-limited substrings that may not be released by mismatch, a control strategy combining the inverter MPPT to lower the voltage of the PV string is proposed for ensuring that all the modules in the string are released. The results of actual test verifications show that the proposed strategy can effectively reduce the voltage of PV modules and strings. The number of PV modules in each string of 1000 V and 1500 V systems can be increased by 5 and 8, respectively, and the capacity of each string can be increased by more than 20%, such that great practical application and potential for reducing the cost of PV system can be achieved.